Dampak ekspor ke tiga negara di kawasan Selat Malaka terhadap penyerapan tenaga kerja Indonesia di sektor pertanian - Emilia, Emilia; Nurjanah, Rahma (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to analyze the development of Indonesia's exports to the three countries in the Malacca Strait of Malaysia, Singapore, and Thailand from 1990-2014 and analyzed the effect of exports to these three countries on the absorption of Indonesian labor in the agricultural sector. The result of the research show during the period from 1990- 2014 the value of Indonesia's exports to Malaysia fluctuated or fluctuated with an average value of 3,906.52 million US Dollars and with an average growth of 17.49%,. The value of Indonesian exports to Thailand fluctuated or fluctuated with an average value of 2,255.28 million US dollars with an average growth of 17.11%. During the period of growth, the highest occurred in 1998 which amounted to 13.29% and the lowest growth occurred in 1997 that is -7.76%. First, second and third model regression results show that Indonesia's export value to Malaysia, Singapore, and Thailand has no significant effect on the absorption of labor in the agriculture sector